Absence of Internal Radiation Contamination by Radioactive Cesium among Children Affected by the Fukushima Daiichi Nuclear Power Plant Disaster. Issue 1 (January 2015) - Tsubokura, Masaharu; Kato, Shigeaki; Nomura, Shuhei; Morita, Tomohiro; Sugimoto, Amina; Gilmour, Stuart; Kami, Masahiro; Oikawa, Tomoyoshi; Kanazawa, Yukio
<x xml:space="preserve">Abstract</x> Abstract Chronic internal radiation contamination accounts for a substantial fraction of long-term cumulative radiation exposure among residents in radiation-contaminated areas. However, little information is available on ongoing chronic internal radiation contamination among residents near the crippled Fukushima Daiichi nuclear power plant. Using a whole body counter, internal radiation contamination levels among elementary and middle school students who commute to 22 schools located within Minamisoma city were assessed between May and July 2013 (26 to 28 mo after the disaster). Of 3, 299 elementary and middle school students in the city, 3, 255 individuals (98%) were screened through school health check-ups. Not a single student was detected with internal radiation contamination due to radioactive cesium. The study found no risk of chronic internal radiation exposure among residents near the crippled nuclear power plant. Current food inspection by local governments, volunteers, and farmers has been functioning well within Fukushima prefecture. However, food management by screening suspected contamination along with whole body counter screening are key public health interventions and should be continued to avoid further internal radiation exposure in radiation-contaminated areas.